PENDEKATAN KOGNITIF SOSIAL PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Sultansyah, Panji; M. Royhan Laverdho; Muhammad Naufal Gustrianto (STAI Ma'had Aly Al-Hikam Malang, 2024)
Abstract The purpose of this study is to find out about the form of social cognitive theory approach from Bandura which can be applied to the learning of Islamic Education in Schools. Based on several previous studies, the cognitive approach has widely applied to learned was the cognitive approach from Piaget. The method used in this research is qualitative research with library research approach. Based on the analysis of the literature study, the approach of the social cognitive theory that can be applied to the learning of Islamic Education learning is through observational learning or modeling which includes four processes namely the process of attentional, retention, reproduction, and motivational processes. The social-cognitive approach that can be applied to Islamic education learning is on the application; curriculum, teaching, and assessment. In addition, the application of social learning theory by means of modeling is not contrary to the teachings of Islam that encourage people to make the Prophet as a model or role model in life. Keywords : Social cognitive theory; Modeling; Islamic education learning Abstract Tujuan penelitian ini adalah untuk mengetahui bentuk pendekatan teori kognitif sosial dari Bandura yang dapat diterapkan pada pembelajaran Pendidikan Agama Islam di Sekolah. Berdasarkan beberapa penelitian terdahulu, pendekatan kognitif yang banyak diterapkan dalam pembelajaran adalah pendekatan kognitif dari Piaget. Metode yang digunakan dalam penelitian ini adalah penelitian kualitatif dengan pendekatan penelitian kepustakaan. Berdasarkan analisis studi literatur, pendekatan teori kognitif sosial yang dapat diterapkan pada pembelajaran Pendidikan Agama Islam adalah melalui pembelajaran observasional atau pemodelan yang mencakup empat proses yaitu proses atensi, retensi, reproduksi, dan motivasi. . Pendekatan sosial-kognitif yang dapat diterapkan dalam pembelajaran pendidikan agama Islam ada pada penerapan; kurikulum, pengajaran, dan penilaian. Selain itu, penerapan teori pembelajaran sosial melalui keteladanan tidak bertentangan dengan ajaran Islam yang menganjurkan umat untuk menjadikan Nabi sebagai teladan atau panutan dalam kehidupan. Kata Kunci : Teori kognitif sosial; pemodelan; Pembelajaran pendidikan Islam